KESALAHAN â€“ KESALAHAN GRAMATIKAL BAHASA INGGRIS DALAM KARANGAN DESKRIPTIF OLEH SISWA SMK N.1 AMURANG - Runtuwene, Winly Jovi (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT This skripsi, entitled â€œKesalahan â€“ kesalahan Gramatikal dalam Karangan Deskriptif oleh Siswa SMK N.1 Amurangâ€, is an attempt to identify and analyze the types of errors in English grammar in descriptive writing made by grade XI of SMK N. 1 Amurang. The data were taken from the studentsâ€™ writing homework. All data concerning grammatical errors were analyzed by using Lennonâ€™s theory. The method used in this research is descriptive. The result of this research shows that there are four kinds of errors made by the students. Those four kinds of errors are first, addition is a grammatical error by adding a part which is unnecessary. Second, omission is a grammatical error by eliminate a part which is necessary. Third, substitution is a grammatical error by using some grammar to another grammar. And the last, ordering is a grammatical error by locate some words into wrong order. This research is expected to give a contribution to the study of linguistics and to help students in identifying errors in English that are commonly made by Indonesian learner. Â  Keywords : Grammatical errors, error analysis, addition, omission, substitution, andÂ Â Â Â Â Â Â Â Â Â  ordering